Laser cladding double-phase high-entropy alloy coating and preparation method thereof
The preparation of the biphasic high-entropy alloy coating through laser cladding technology solves the problems of high brittleness, high crack sensitivity and poor high-temperature oxidation resistance of the existing coating, and achieves the low brittleness, high wear resistance and excellent high-temperature oxidation resistance of the coating.
Patent Information
- Application Number
- CN202411924485.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing high-entropy alloy coatings have high performance brittleness, high crack sensitivity and poor high-temperature oxidation resistance, which is difficult to meet the application needs under extreme operating conditions.
The dual-phase high-entropy alloy coating is prepared by laser cladding technology. By adjusting the element composition and process parameters, the brittleness of the coating is reduced, its high-temperature oxidation resistance and wear resistance are improved, and the orderly B2 phase is formed by introducing Ni elements to regulate the microstructure.
The coating is achieved with low brittleness, high wear resistance and excellent high temperature oxidation resistance, extends the service life of the substrate and reduces the consumption of development resources.
Smart Images

Figure CN119685675A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser surface modification, and in particular to a laser cladding dual-phase high entropy alloy coating and a preparation method thereof. Background Art
[0002] High entropy alloys are a new type of metal material with a unique design strategy. The alloy composition is composed of five or more elements mixed in an equimolar ratio or a near equimolar ratio, with the concentration of each element ranging from 5% to 35%. Under the action of high mixing entropy, the system tends to form a single-phase solid solution. This method breaks through the design concept of traditional alloys and expands the composition design from the corner of the phase diagram to the center, thereby achieving excellent comprehensive performance.
[0003] Since the concept of high entropy alloys was proposed, domestic and foreign researchers have conducted a lot of systematic research on them. Initially, the phase structure was stabilized by maximizing the entropy value to obtain excellent and stable performance, but this method has certain limitations (a simple microstructure of the physical phase is obtained, but it also limits its performance upper limit). Therefore, the strict restrictions on the composition were relaxed, and attempts were made to adjust the alloy elements or components to achieve a multiphase structure to further improve the strength and toughness of the alloy and reduce the brittleness of the alloy, but the results were not very ideal. Therefore, it is urgent to find a method that can break through the above limitations to obtain alloy coating materials with better performance. Summary of the invention
[0004] The purpose of the present invention is to provide a laser cladding dual-phase high entropy alloy coating and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The laser cladding dual-phase high entropy alloy coating of the present invention has low brittleness, reduces the crack sensitivity of the laser cladding coating, has good quality and excellent comprehensive performance.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a laser cladding dual-phase high entropy alloy coating, which includes the following raw materials, in atomic percentage: Al is 9-16%, Cr is 11-17%, Fe is 11-18%, Ti is 13-20%, V is 10-15%, and Ni is 28-33%.
[0007] Technical solution 2 of the present invention: A method for preparing the above-mentioned laser cladding dual-phase high entropy alloy coating comprises the following steps:
[0008] The raw materials are mixed and ball-milled to obtain alloy powder, the alloy powder is pre-placed on the surface of the substrate, and laser cladding is performed after drying to obtain the laser cladding dual-phase high entropy alloy coating.
[0009] Furthermore, the ball-to-material ratio of the ball mill is 5:1, the rotation speed is 100-140 rpm, and the time is 6-10 hours.
[0010] Furthermore, the ball milling method is to alternately perform forward rotation and reverse rotation with a pause of 10 to 20 minutes in between; the forward rotation time is 20 to 30 minutes, and the reverse rotation time is 20 to 30 minutes.
[0011] Furthermore, the particle size of the raw material is 15 to 53 μm; the preset thickness of the alloy powder is 0.7 to 1.3 mm.
[0012] Furthermore, the drying temperature is 60-80° C. and the drying time is 6-8 hours.
[0013] Furthermore, the surface area ratio of the substrate to the preset area of the alloy powder is 14 mm 2 :4mm 2 ; The alloy powder is pre-placed in the middle of the substrate.
[0014] Furthermore, the conditions for the laser cladding include: an output power of 600-850 W, a spot diameter of 3-4 mm, a laser scanning speed of 200-350 mm / min, and an inert atmosphere.
[0015] Furthermore, the substrate includes a titanium alloy substrate (such as a TC4 titanium alloy substrate).
[0016] Technical solution three of the present invention: an application of the above-mentioned laser cladding dual-phase high entropy alloy coating in the aerospace field.
[0017] The present invention discloses the following technical effects:
[0018] (1) The laser cladding dual-phase high-entropy alloy coating of the present invention has good high-temperature oxidation resistance and wear resistance, and can match the thermophysical properties of the TC4 titanium alloy substrate. The cladding layer has no obvious defects and forms a metallurgical bond with the substrate, which can extend the service life of the TC4 titanium alloy, broaden its application scenarios in extreme working conditions, and greatly save the development resources of the TC4 titanium alloy.
[0019] (2) The present invention introduces the Ni element into the laser cladding dual-phase high entropy alloy coating, utilizes Al / Ni to form an ordered B2 phase with the same BCC structure, and regulates the microstructure of the coating, thereby improving the comprehensive performance of the coating (less brittleness, good wear resistance, and a wear rate of only 12.8% of that of the TC4 titanium alloy substrate).
[0020] Furthermore, the laser cladding dual-phase high entropy alloy coating of the present invention has excellent oxidation resistance in air at 800° C., and compared with the TC4 titanium alloy substrate, the oxidation rate of the coating is reduced by 55%.
[0021] (3) The present invention lays the mixed alloy powder on the surface of the TC4 titanium alloy substrate by a pre-placement method, and irradiates the powder with a high-energy laser beam to obtain a coating that is metallurgically bonded to the substrate, has good forming quality and good comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a cross-sectional morphology of the laser cladding dual-phase high entropy alloy coating prepared in Example 1 of the present invention;
[0024] Figure 2 XRD spectra of the laser cladding dual-phase high entropy alloy coating prepared in Example 1 of the present invention, the high entropy alloy coating prepared in Comparative Example 1, and the high entropy alloy coating prepared in Comparative Examples 1-2;
[0025] Figure 3 The SEM and element distribution diagram of the laser cladding dual-phase high entropy alloy coating prepared in Example 1 of the present invention;
[0026] Figure 4 Wear rate diagram of the TC4 titanium alloy substrate (Ti6Al4V) used in the present invention, the laser cladding dual-phase high entropy alloy coating prepared in Example 1, the high entropy alloy coating prepared in Comparative Example 1, and the high entropy alloy coating prepared in Comparative Examples 2 to 3;
[0027] Figure 5 The oxidation weight gain curves are of the TC4 titanium alloy substrate (Ti6Al4V) used in the present invention, the laser cladding dual-phase high entropy alloy coating prepared in Example 1, the high entropy alloy coating prepared in Comparative Example 1, and the high entropy alloy coating prepared in Comparative Examples 2 to 3. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] Example 1
[0034] A preparation method of laser cladding dual-phase high entropy alloy coating:
[0035] (1) The laser cladding dual-phase high entropy alloy coating is composed of the following raw materials, in atomic percentage: Al: 14%, Cr: 14%, Fe: 14%, Ti: 14%, V: 14%, and Ni: 30%.
[0036] (2) Al powder, Cr powder, Fe powder, Ti powder, V powder and Ni powder were weighed out according to atomic percentage using an electronic balance with an accuracy of ±0.1 mg (all powders were commercial spherical powders with a particle size of 15 to 53 μm).
[0037] (3) The raw material powders are mixed according to the proportion and placed in a ball mill with a ball-to-material ratio of 5:1, a stainless steel ball with a diameter of 3 mm, and a rotation speed of 120 rpm for ball milling. During ball milling, forward rotation and reverse rotation are performed alternately. The forward rotation time is 20 min, the reverse rotation time is 20 min, and a pause of 15 min in the middle is one ball milling cycle. The mixing is continued for 10 h to obtain alloy powder.
[0038] (4) The TC4 titanium alloy was cut into plates of 40 mm × 14 mm × 4 mm by wire cutting, and then the oxides and oil stains on the surface of the TC4 titanium alloy were removed by rough grinding with 400-mesh metallographic sandpaper. The alloy was placed in alcohol ultrasonic treatment for 10 min and then dried to obtain the TC4 titanium alloy substrate.
[0039] (5) The alloy powder is pre-placed on the surface of the TC4 titanium alloy substrate. The pre-placed powder size is 40 mm×4 mm×1 mm and is pre-placed in the middle of the substrate surface to obtain a prefabricated sample.
[0040] (6) The prefabricated sample was placed in a vacuum dryer and dried at 80°C for 6 h to obtain a dried sample.
[0041] (7) Place the dried sample in a fiber laser irradiation device and release argon for 5 min before irradiating with 15 L / min - 1 Argon was continuously supplied at a speed of 1000 nm, and the laser output power was controlled to be 800 W, the spot diameter was 3 mm, and the laser scanning speed was 300 mm / min to irradiate the preset layer with fiber laser. After irradiation, argon was supplied for 5 min until the sample was completely cooled to obtain a laser cladding dual-phase high entropy alloy coating (named Al based on the atomic weight ratio). 14 Cr 14 Fe 14 Ti 14 V 14 Ni 30 )'s TC4 titanium alloy.
[0042] Comparative Example 1
[0043] The same as Example 1, except that the alloy coating (AlCrFeTiV) is composed of the following raw materials, by mass percentage: Al 12wt.%, Cr 22wt.%, Fe 24wt.%, Ti 21wt.%, V 21wt.% (atomic percentage is 1:1:1:1:1).
[0044] Comparative Example 2
[0045] The same as Example 1, except that the laser cladding dual-phase high entropy alloy coating is composed of the following raw materials in atomic percentage: Al 16%, Cr 16%, Fe 16%, Ti 16%, V 16%, Ni 20%.
[0046] Comparative Example 3
[0047] The same as Example 1, except that the laser cladding dual-phase high entropy alloy coating is composed of the following raw materials in atomic percentage: Al 18%, Cr 18%, Fe 18%, Ti 18%, V 18%, Ni 10%.
[0048] Effect Example 1
[0049] The cross-sectional morphology of the laser cladding dual-phase high entropy alloy coating prepared in Example 1 is shown in Figure 1 .
[0050] from Figure 1 It can be seen from the figure that there are no obvious cracks in the coating and it forms a metallurgical bond with the titanium alloy substrate. In addition, it can be seen from its bonding line that the dilution rate of the substrate is not high, which can effectively guarantee the comprehensive performance of the coating.
[0051] Laser cladding dual-phase high entropy alloy coating (Ni 30 ), the high entropy alloy coating (AlCrFeTiV) prepared in Comparative Example 1, the high entropy alloy coating (Ni 20 ), the high entropy alloy coating (Ni 10 )’s XRD pattern is shown in Figure 2 .
[0052] from Figure 2 It can be seen that with the introduction of Ni element, Laves' diffraction peak appears in the coating. When the atomic ratio of Ni element is 30%, a small diffraction peak appears at about 30 degrees, which is judged to be B2 ordered phase.
[0053] Effect Example 2
[0054] The SEM and element distribution diagram of the laser cladding dual-phase high entropy alloy coating prepared in Example 1 are shown in Figure 3 .
[0055] from Figure 3 It can be seen that there are two kinds of contrasting morphologies in the coating. The EDS surface scanning results show that the B2 phase is mainly enriched in Al and Ni elements.
[0056] Effect Example 3
[0057] The wear resistance of the coating was evaluated using a multifunctional wear tester (UMT-2). 3 N 4 Ceramic balls were used as friction pairs and the wear test was carried out using the reciprocating wear method. Coating (TC4 titanium alloy substrate ( Figure 4Ti6Al4V in), the coating prepared in Example 1 ( Figure 4 Ni 30 ), the coating prepared in Comparative Example 1 ( Figure 4 AlCrFeTiV) in the comparative example 2) Figure 4 Ni 20 ) or the coating prepared in Comparative Example 3 ( Figure 4 Ni 10 ) Wear tests were carried out under a load of 20 N, with a wear scar length of 2 mm, an oscillation frequency of 1 Hz, and a wear duration of 30 min. The wear rate results were obtained from the corresponding wear volume, applied load, and total sliding distance, see Figure 4 .
[0058] from Figure 4 It can be seen that the wear rate of TC4 titanium alloy substrate is 3.45×10 -4 mm 3 ·N -1 ·m -1 The wear rate of AlCrFeTiV high entropy alloy coating is 2.89×10 -4 mm 3 ·N -1 ·m -1 With the introduction of Ni element, the wear rate of the coating decreased significantly. The wear rate of the laser cladding dual-phase high entropy alloy coating prepared in Example 1 was only 0.44×10 - 4 mm 3 ·N -1 ·m -1 , greatly improving the wear resistance of the coating.
[0059] Effect Example 4
[0060] The TC4 titanium alloy substrate (i.e., Ti6Al4V), the laser cladding dual-phase high entropy alloy coating (i.e., Ni 30 ), the high entropy alloy coating prepared in Comparative Example 1 (i.e., AlCrFeTiV), the high entropy alloy coating prepared in Comparative Example 2 (i.e., Ni 20 ), the high entropy alloy coating prepared in Comparative Example 3 (i.e. Ni 10 ) were placed in a box furnace and oxidized at 800°C in air for 0.5, 5, 15, 30 and 50 h. The samples were then cooled to room temperature and the weight differences of the samples were recorded using an electronic scale with an accuracy of ±0.1 mg. The results are shown in Figure 5 .
[0061] from Figure 5It can be seen that the laser cladding dual-phase high entropy alloy coating prepared in Example 1 of the present invention has significantly reduced oxidation weight gain under the condition of 800°C in air, and its oxidation rate is only 55% of that of the TC4 titanium alloy substrate. And when the atomic ratio percentage of the Ni element is 30%, its high-temperature oxidation resistance is the best.
[0062] Through research, it is found that the high entropy alloy coating prepared in Comparative Example 1 is a single-phase BCC high entropy alloy coating. The single-phase BCC high entropy alloy coating has significantly more cracks. During the grinding and polishing process, the coating is brittle and small particles fall off. In addition, the high-temperature oxidation resistance and wear performance are significantly reduced. In Example 1, due to the introduction of the Ni element, the precipitation of the Al / Ni ordered B2 phase with the same structure as BCC is promoted, which can not only effectively regulate the forming quality of the coating, but also further improve the comprehensive performance of the coating.
[0063] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A laser cladding dual-phase high entropy alloy coating, characterized in that: In terms of atomic percentage, the following raw materials are included: Al is 9-16%, Cr is 11-17%, Fe is 11-18%, Ti is 13-20%, V is 10-15%, and Ni is 28-33%.
2. A method for preparing a laser cladding dual-phase high entropy alloy coating according to claim 1, characterized in that: The following steps are involved: The raw materials are mixed and ball-milled to obtain alloy powder, the alloy powder is pre-placed on the surface of the substrate, and laser cladding is performed after drying to obtain the laser cladding dual-phase high entropy alloy coating.
3. The preparation method according to claim 2, characterized in that: The ball-to-material ratio of the ball mill is 5:1, the rotation speed is 100-140 rpm, and the time is 6-10 hours.
4. The preparation method according to claim 3, characterized in that: The ball milling method is to alternately perform forward rotation and reverse rotation, with a pause of 10 to 20 minutes in between; the forward rotation time is 20 to 30 minutes, and the reverse rotation time is 20 to 30 minutes.
5. The preparation method according to claim 2, characterized in that: The particle size of the raw material is 15-53 μm; the preset thickness of the alloy powder is 0.7-1.3 mm.
6. The preparation method according to claim 2, characterized in that: The conditions for laser cladding include: output power of 600-850W, spot diameter of 3-4mm, laser scanning speed of 200-350mm / min, and inert atmosphere.
7. The preparation method according to claim 2, characterized in that: The substrate includes a titanium alloy substrate.
8. Application of the laser cladding dual-phase high entropy alloy coating according to claim 1 in the field of aerospace.
Citation Information
Patent Citations
High-entropy alloy bionic gradient structure composite coating with eutectic interface and preparation method thereof
CN114196952A
Preparation method and application of strengthened high-entropy alloy coating
CN117107233A
AlCoCrFeNi series biphase carbide enhanced laser cladding high-entropy alloy composite coating and preparation method thereof
CN118756135A
System for managing creation cost of brand
KR1020240093399A
High-entropy alloy powder, coating thereof, and preparation method for coating
WO2023246119A1